MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI VIDIO PEMBELAJARAN BERBASIS SOSIAL MEDIA PADA PELAJARAN INFORMATIKA UNTUK KELAS 7 SMP 29 MALANG - Yanuar Eko Ardiansyah; Azhar Ahmad Smaragdina; Dion Dwi Rizky; Dhea Widyaningrum; Francisca Anindya Mayta Prasasti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to develop Problem-Based Learning (PBL)-based instructional videos accessible across devices to enhance seventh-grade students’ understanding of informatics at SMPN 29 Malang. The research employed a quasi-experimental method with a pretest-posttest design, using instruments including pretests, posttests, and student activity observation sheets. The results showed that the initial average pretest score was 40.94, increasing slightly to 44.22 before the implementation of PBL. After applying the PBL model, a significant improvement was observed: 64.06 in Cycle 1 and 75.94 in Cycle 2. The N-Gain scores were 0.46 in Cycle 1 and 0.62 in Cycle 2, both categorized as moderate to relatively high. Student engagement was also considered active, with an average score of 3.13 on a 1–4 Likert scale, indicating meaningful participation during the learning process. These findings suggest that PBL-based instructional videos are effective in improving both students' conceptual understanding and learning engagement, aligning with previous studies that highlight the strengths of the PBL model.